Retrospective study of rotavirus in beef and dairy herds in the State of São Paulo, Brazil - de Godoy Siqueira, Heloisa Pinto [UNESP]; Hoppe, Ingrid Bortolin Affonso Lux [UNESP]; de Siqueira, André Buzutti; da Gloria Buzinaro, Maria [UNESP] (My University, 2018)
Rotavirus is a major cause of neonatal diarrhea in cattle worldwide, leading to significant economic losses. This study aimed to determine the occurrence of rotavirus infection in 48 herds of dairy and beef cattle from 21 municipalities in the northern region of São Paulo State, Brazil during 2006-2010. A total of 803 fecal samples from calves aged 1-90 days were analyzed by polyacrylamide gel electrophoresis (PAGE), and positive samples were detected in 33.3% (16/48) of the herds and 6.1% (49/803) of the samples. Of the 326 samples from calves with diarrhea, 12.6% (41/326) were positive, while only 1.7% (8/477) of the 477 samples from calves without clinical signs were positive. These results showed that there is a statistically significant association between the presence of diarrhea and rotavirus infection. Of the 35 dairy herds studied, 34.3% (12/35) were positive for rotavirus, and 3.3% (23/689) of the samples were positive. Of the samples from animals with diarrhea, 5.6% (15/269) were positive, while 1.9% (8/420) of the samples from animals without diarrhea were positive. Chi-square analysis showed a significant association between rotavirus detection and the presence of diarrhea in dairy herds. However, there was no statistical relationship between the age of the calves and rotavirus infection. Of the 13 beef herds sampled, 30.8% (4/13) had positive animals, and 22.8% (26/114) of the samples were positive. All of the positive animals had diarrhea (26/26), which resulted in undefined statistical association. However, the frequency of positive samples was significantly higher in calves aged 1-30 days (p < 0.05). According to the migration of the rotavirus genome in PAGE, it was possible to identify seven distinct electrophoretic types, characteristic of group A rotaviruses, showing genetic differences among the detected strains. The presence of rotavirus infections in the studied region emphasizes the importance of implementing control and prevention measures, since the agent is in constantly evolving in cattle herds.
Estudo retrospectivo de rotavírus bovino em rebanhos leiteiros e de corte no Estado de São Paulo, Brasil
Keywords: Calves; Diarrhea; Electrophoretic profile; PAGE